Analisis Pemasaran Media Sosial terhadap Sikap Merek melalui Kesadaran Merek dan Citra Merek pada Institusi Pendidikan - Evi Zulfiah; Muinah Fadhilah; Ambar Lukitaningsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The study discusses social media, especially Instagram, which is now used as one of the main sources for finding information. Instagram is currently a platform that must be owned by companies as a branding medium. Branding is a strategy to introduce, build and grow a brand until it is known and gets loyalty from the public. The purpose of this study is to determine the effect of social media marketing on brand attitudes, brand awareness and brand image. To determine the effect of brand awareness on brand attitudes and brand image. To determine the effect of brand image on brand attitudes. This type of research is quantitative research with a survey method. The number of samples in this study studied was 100 samples. Purposive sampling method, questionnaire data collection method. Data analysis techniques using Structural Equation Modeling (SEM) with the SmartPLS program. The results of the study showed a positive and significant effect between social media marketing on brand attitudes, brand awareness and brand image. There is a positive and significant effect between brand awareness on brand attitudes and brand image. There is a positive and significant effect between brand image on brand attitudes.